The Effect of Heterogeneity on the Distribution and Treatment of PFAS in a Complex Geologic Environment - McGregor, Rick; Benevenuto, Leticia (Frontiers in Environmental Chemistry, 2021)
Per- and polyfluoroalkyl substances (PFAS) have been identified as emerging contaminants of concern in the environment in a wide variety of media including groundwater. Typically, PFAS-impacted groundwater is extracted by pump and treat systems and treated using activated carbon and ion exchange resin. Pump and treat systems are generally considered ineffective for the remediation of contaminants including PFAS but instead used for plume containment. The demonstrated use of in-situ treatment for PFAS-impacted groundwater is limited with only colloidal activated carbon (CAC) being shown to effectively attenuate PFAS over short and moderate time periods. Topics of active study for the in-situ treatment of PFAS include the effect of heterogeneity on the distribution of the CAC, the lifespan of the CAC itself, the effect of competitive adsorption/absorption and the effect of other geochemical conditions on the removal process. This study looked at the effect of heterogeneity on the treatment, distribution, and projected lifespan of CAC at a site with complex geology. The site’s geology varied from a silty sand to sand to fractured bedrock. Parameters evaluated included the distribution of the CAC as well as the subsequent treatment of the PFAS and other dissolved contaminants including benzene, toluene, ethylbenzene, and xylene. Results of groundwater sampling indicated that the PFAS detected within the groundwater were treated effectively to below their respective detection limits for the duration of the one-year test in both the silty sand and sand aquifers. The PFAS within the groundwater in the fractured rock aquifer showed a different treatment profile with longer carbon chained PFAS being attenuated preferentially compared to shorter carbon chained PFAS suggesting that competitive adsorption/absorption reactions were occurring on the adsorption/absorption sites. Analysis of the unconsolidated aquifer cores determined that direct push injection of the CAC was effective at delivering the colloidal activated carbon to the target injection zone with post-injection total organic carbon (TOC) concentrations increasing by up to three orders of magnitude compared to pre-injection TOC concentrations. Heterogeneity did have a significant impact on the CAC distribution with higher hydraulic conductivity seams receiving more mass of CAC than lower hydraulic conductivity zones.